2019
DOI: 10.1111/iej.13086
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility, bioactive potential and antimicrobial activity of an experimental calcium silicate‐based endodontic sealer

Abstract: Aim To evaluate the cytocompatibility, bioactive potential, antimicrobial and antibiofilm activities of an experimental calcium silicate‐based endodontic sealer, in comparison with TotalFill BC Sealer and AH Plus. Methodology Cytocompatibility was assessed by methyltetrazolium (MTT) and neutral red (NR) assays, after exposure of the Saos‐2 cells to the sealer extracts (1 : 2, 1 : 4, 1 : 8, 1 : 16 and 1 : 32 dilutions) for 24 h. The sealers were manipulated and placed in 12‐well culture plates and exposed to ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 36 publications
9
54
0
2
Order By: Relevance
“…Alizarin Red assay was assessed to evaluate mineralization capacity of the root repair cements; both cements produced more calcium deposits than the negative control, confirming the inductive effect of both root repair materials on the mineralization and differentiation of hPDLSCs. Previous reports have shown that putty calcium silicate materials induced mineralization [25,27]. Calcium silicates are the main components of both cements (Table 1) which justifies the result obtained.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Alizarin Red assay was assessed to evaluate mineralization capacity of the root repair cements; both cements produced more calcium deposits than the negative control, confirming the inductive effect of both root repair materials on the mineralization and differentiation of hPDLSCs. Previous reports have shown that putty calcium silicate materials induced mineralization [25,27]. Calcium silicates are the main components of both cements (Table 1) which justifies the result obtained.…”
Section: Discussionsupporting
confidence: 87%
“…TFB and BCR showed similar results in terms of cell viability as compared with a control group. In line with this work, previous reports have described similar results, also using the MTT test with TotalFill BC sealer, which has an almost identical composition, except it changes consistency [25,26]. Benetti et al [27] also reported that BCR is a biocompatible material that induces mineralization in vivo.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings showed that Apexit Plus had an effective antibacterial action against Enterococcus faecalis, a facultative anaerobic Gram-positive coccus responsible for root canal treatment failures [34]. Here, the findings were obtained using the direct contact test for 60 minutes, a widely used methodology performed to assess the antimicrobial activity of materials [35,36]. The antimicrobial properties of calcium hydroxide-based sealers has been related to hydroxyl ion release and, consequently, to an increased alkaline pH in the environment promoted by fresh sealers [4].…”
Section: Biological Propertiesmentioning
confidence: 83%
“…Since Mosmann (1983) proposed a fast tetrazolium salt-based colorimetric test (MTT) with applicability for the evaluation of cell viability/cell proliferation, this and other tetrazolium salt-based tests such as XTT (Scudiero et al 1988), MTS (Barltrop et al 1991) and WST-1 (Tan & Berridge 2000) have been widely used in the screening of cytotoxic effects of diverse substances (Vbrova et al 2016, Tao et al 2016 and materials, including those intended for root canal filling (Osorio et al 1998, Zordan-Bronzel et al 2019. These tests are based on the ability of metabolically active cells to produce reduced pyridine nucleotides, which act as substrates for cellular oxidoreductases, and are responsible for the process of reduction of tetrazolium salts into formazan salts (Tan & Berridge 2000).…”
Section: Discussionmentioning
confidence: 99%